Cyclic stretch enhances the expression of Toll-like Receptor 4 gene in cultured cardiomyocytes via p38 MAP kinase and NF-κB pathway - Wang Bao-Wei; Shyu Kou-Gi; Lin Chiu-Mei; Chang Hang (Journal of Biomedical Science, 2010)
Abstract Background Toll-like receptor 4 (TLR4) plays an important role in innate immunity. The role of TLR4 in stretched cardiomyocytes is not known. We sought to investigate whether mechanical stretch could regulate TLR4 expression, as well as the possible molecular mechanisms and signal pathways mediating the expression of TLR4 by cyclic mechanical stretch in cardiomyocytes. Methods Neonatal Wistar rat cardiomyocytes grown on a flexible membrane base were stretched by vacuum to 20% of maximum elongation at 60 cycles/min. Western blot, real-time polymerase chain reaction, and promoter activity assay were performed. In vitro monocyte adhesion to stretched myocyte was detected. Results Cyclic stretch significantly increased TLR4 protein and mRNA expression after 2 h to 24 h of stretch. Addition of SB203580, TNF-α antibody, and p38α MAP kinase siRNA 30 min before stretch inhibited the induction of TLR4 protein. Cyclic stretch increased, while SB203580 abolished the phosphorylated p38 protein. Gel shifting assay showed significant increase of DNA-protein binding activity of NF-κB after stretch and SB203580 abolished the DNA-protein binding activity induced by cyclic stretch. DNA-binding complexes induced by cyclic stretch could be supershifted by p65 monoclonal antibody. Cyclic stretch increased TLR4 promoter activity while SB203580 and NF-κB siRNA decreased TLR4 promoter activity. Cyclic stretch increased adhesion of monocyte to cardiomyocytes while SB203580, TNF-α antibody, and TLR4 siRNA attenuated the adherence of monocyte. TNF-α and Ang II significantly increased TLR4 protein expression. Addition of losartan, TNF-α antibody, or p38α siRNA 30 min before Ang II and TNF-α stimulation significantly blocked the increase of TLR4 protein by AngII and TNF-α. Conclusions Cyclic mechanical stretch enhances TLR4 expression in cultured rat neonatal cardiomyocytes. The stretch-induced TLR4 is mediated through activation of p38 MAP kinase and NF-κB pathways. TLR4 up-regulation by cyclic stretch increases monocyte adherence.